Enhancing the Water Stress Factors for Simulation of Corn in RZWQM2. (1st January 2014) - Saseendran, S.A.; Ahuja, L. R.; Ma, L.; Nielsen, D. C.; Trout, T. J.; Andales, A. A.; Chávez, J. L.; Ham, J.
Abstract : Enhancement of agricultural system models for more accurate simulations of the water stress response of crops can improve their application under limited water management. Currently, the crop system model RZWQM2 uses a ratio of potential root water uptake (supply) to potential transpiration (demand) as a water stress factor (WSDef) that modulates plant growth processes. We tested two progressive modifications of the WSDef (WSI1 and WSI2) in the DSSAT‐CSM‐CERES‐Maize (Version 4.0) module embedded within the RZWQM2 model for simulating the response of corn ( Zea mays L.) to different levels of water and compared them with the use of WSDef. The WSI1 was a modification of the SWFAC (Soil Water FACtor) for photosynthesis‐related processes in RZWQM2 using the daily potential root water uptake (TRWUP) calculated by the Nimah and Hanks approach. The WSI2 was WSI1 with terms accounting for stress due to additional heating of the canopy from unused energy of potential soil evaporation in both the supply and demand terms of the WSI1. These factors were evaluated using the data for corn grain yield, biomass, soil water, and leaf area index (LAI) derived from canopy cover data from multiple water‐level experiments conducted at Greeley, CO, from 2008 to 2011, irrigated and rainfed corn at Akron, CO, and irrigated corn at Gainesville, FL, on different soil types. Overall, the stress factors WSI1 and WSI2 were found to be superior to WSDef in simulations of grain yield, biomass, and LAI in all three experiments. Further, in general, WSI2 simulations of the crop were either comparable to or more accurate than WSI1 simulations in most of the crop seasons simulated in this study. The stress factor WSI2 has been incorporated in the RZWQM2 for simulating corn.